Computer Assisted Case Analyses. - Howkins, David; Allen, Brandt (The Accounting Review, 1967)
Abstract Harvard Business School, Cambridge, Massachusetts gave its students of graduate business administration access to special time-sharing computer programs to assist them in preparing for financial accounting case discussions. The preliminary results of this experiment indicate this use of computers can lead to a more through understanding by the students into a greater number of possible alternative solutions to case problems. Significant improvement in the performance of the less quantitatively oriented students. Heightened student interest and increased motivation toward the course. The case studies are based on actual business situations where a management faces a decision involving alternative accounting policies, such as whether a company should account for a merger on the "pooling" or "purchase" basis. A large number of the cases deal with the very controversial areas of financial reporting such as pensions, leases, business combinations, deferred taxes, etc. These cases are approached from a management point of view giving consideration to the potential investor, the public interest, the present stockholders, and the company's independent auditor.